A Primer to Understanding the Elements of Medical Malpractice - Hill, Gregory Q.; Ryu, Robert K. (Seminars in Interventional Radiology, 2019)
According to a 2017 survey of 4,000 physicians across 25 different specialties in the United States, 55% of respondents report having been sued at least once, with nearly half of them having been sued multiple times. In addition, procedural specialists are far more likely to be sued. As a procedural-driven specialty, interventional radiology (IR) practitioners are subject to these statistics. While the focus of all IR practices is providing the highest quality care safely and efficiently, medical errors and complications are unavoidable. Understanding the process of medical malpractice litigation is necessary to develop strategies on how best to avoid and mitigate the hardships of the process.
Keywords: medical malpractice; medical error; medical complications; litigation; interventional radiology